Aktivitas Protease dan Komposisi Proksimat Tubuh Ikan Sidat (Anguilla bicolor Mcclelland) pada Kondisi Puasa dan Pemberian Pakan Kembali - Untung Susilo; Nuning Setyaningrum; Farida Nur Rachmawati (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2013)
Protease activity and body proximate composition of eel, Anguilla bicolor McClelland., under starvation and refeeding conditions with three treatments and four replications in randomized completely design has been evaluated. The result showed that the protease activity of eel was no significant different (P>.05) between treatment, but body proximate composition has significant differences (P<.05), especially in protein and lipid contents at starvation condition. It can be concluded that the eel protease activity did not change under starvation and refeeding condition, but the lipid content decreased at starvation condition.